The Application of Khiyar Principles to E-Commerce Transaction: The Islamic Economy Perspective - Hafid, Abd.; Bahri, Syamsul; Marzuki, Sitti Nikmah; Muis, Musrini; Idayanti, Rini (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This essay seeks to analyze the utilization of khiyar in e-commerce transactions within the context of Islamic economics. The principle of khiyar allows individuals to exercise the option to either proceed with or terminate a transaction. This theory is applicable to various types of buying and selling transactions, including those conducted in the realm of e-commerce. This study employs a normative legal methodology with an Islamic economic perspective, which is evaluated descriptively. The data was gathered through an extensive analysis of literary sources, including journal articles, books, journals, legal documents, and other relevant references pertaining to the topic of discussion. Islamic economic theory is applied as an analytical framework to examine the concept of khiyar (option) in the context of buying and selling in e-commerce transactions in Indonesia. The research findings indicate that the utilization of khiyar in e-commerce transactions, in accordance with the Islamic law, is permissible as long as it adheres to the prerequisites and fundamental principles of buying and selling. These include honesty, fairness, and the absence of any fraudulent elements. However, if harm is inflicted upon one of the parties involved, the transaction becomes unlawful. In the Islamic law, there is a rule stating that all forms of muamalah transactions are permissible, as long as there are no contradictory arguments prohibiting them. The contract and payment mechanisms in e-commerce transactions are considered to be in accordance with Islamic law and contain benefits, also in line with the opinion of the ulama in the fatwa of the Indonesian Ulema Council. From an Islamic economic standpoint, engaging in e-commerce transactions for buying and selling is sufficient to contribute to the nation's economic expansion, particularly benefiting the middle class and streamlining transactions.